SAT0285 The physical performance of systemic lupus erythematosus patients with low disease activity: could the cardiopulmonary exercise testing refine its assessment?. (15th June 2017) - Gusetu, G; Mociran, A; Pamfil, C; Damian, L; Pop, D; Zdrenghea, D; Rednic, S
Abstract : Background: Even during remission, the systemic lupus erythematosus (SLE) patients have reduced exercise performance and this contributes to impairment of their quality of life 1 . Several causes as depression and deconditioning, arthritis, anemia, cardiovascular and respiratory involvement are widely accepted; however the weight of each factor is less known in particular individuals. Objectives: Our study aimed to assess through cardiopulmonary exercise testing (CPX) the exercise performance of a SLE cohort and to establish its main determinants. Methods: Thirty-one SLE patients with low disease activity underwent a CPX on cycle ergometer; the main metabolic parameters and standard 12-leads ECG were recorded; before exercise testing, a cardiac Doppler ultrasound was performed. The patient's characteristics, cumulative organ damage and laboratory data were retrieved by medical chart review. The control group consisted of 25 age and sex-matched healthy, non-trained individuals. Results: Within the study group, 28 (90.3%) were female, the mean age was 42.7±10.6 years and disease median duration 7.9 years. The aerobic performance was decreased by 16.2% (17.6 vs 21.36 ml/kg/min, p=0.022); the main disease characteristics which correlated with maximum oxygen uptake (VO2Mx) were anemia (p=0.035), renal involvement (p=0.05) and antiphospholipid syndrome (APS) (p=0.042) but not disease duration, cumulative damage or the immunological tests (hypocomplementemia, anti-Ro, anti-Sm, anti-dsDNA, AAN or APL antibodies). One quarter of patients did not reach the ventilatory anaerobic threshold (VAT, expressed as a percentage of calculated VO2Mx), mainly due to musculoskeletal pain (5 patients), dyspnea (2 patients with history of pulmonary embolism) and sudden rise in blood pressure (1 patient). Among the rest of them (23 patients, 74%), the VAT was at the lower limit of normal range (41.03% vs 54.0% for controls, p=0.014) corresponding to a "training reserve" of 31%. Of particular importance from this point of view were the criteria for test termination: dyspnea in 4 patients (1 with anemia, 1 with pulmonary fibrosis and 2 by hyperventilation proved by mean VE/VCO2 =41.5), fatigue (9 patients) and arthralgia (7 patients). Notably, among patients with established diagnosis of mild pulmonary fibrosis, COPD, ischemic or valvular heart disease, not dyspnea but arthralgia or fatigue was the reason for test termination, even if the VO2Mx was lower than recorded in the rest of the group (15.8 vs 19.2 ml/kg/min, p=0.037). Conclusions: The exercise aerobic capacity of SLE patients is diminished and correlates with anemia, renal involvement and with hystory of pulmonary embolism. Surprisingly, even in patients with mild cardiovascular or respiratory involvement, the decreasing of exercise performance is limited mainly from musculoskeletal symptoms and from deconditioning. References: Carvalho MR, Sato EI, Tebexreni AS, et al. Effects of supervised cardiovascular training program on exercise tolerance, aerobic capacity, and quality of life in patients with systemic lupus erythematosus. Arthritis Rheum 2005;53(6):838–44. Disclosure of Interest: None declared